Attentional biases in older adults with generalized anxiety disorder. (April 2020) - Cabrera, Isabel; Brugos, David; Montorio, Ignacio
Highlights: Older adults with clinical anxiety showed attentional bias to negative information. Older adults with clinical anxiety showed attentional avoidance of positive stimuli. Healthy older adults exhibited the reverse pattern of attentional deployment. Attentional biases seem to be a characteristic of older adults with clinical anxiety. Abstract: Cognitive theories of anxiety propose that selective attention to negative information plays a central role in the development and maintenance of anxiety. The presence of such attentional bias has been confirmed in younger adults. Nevertheless, there are few studies that have explored anxiety-linked attentional bias in older adults, and the available results are inconclusive. Conversely, the socioemotional selectivity theory posits that there are age-related changes in emotional information processing and, consistent with this account, it has been found that older adults preferentially pay more attention to positive stimuli compared with younger adults ("positivity effect"). The present study aimed to explore attentional bias towards negative and positive information in a sample of older adults with generalized anxiety disorder (GAD) compared with a control group. The results showed that older adults with GAD displayed an attentional preference for negative information and attentional avoidance for positive information, whereas healthy older adults showed the reverse pattern of attentional deployment. These results suggest that selective attention toward negative information and selective avoidance of positive information may be a relevant factor in clinically anxious older adults.